Patients' experiences of temporomandibular disorders and related treatment - Aurelia Ilgunas; Anncristine Fjellman-Wiklund; Birgitta Häggman-Henrikson; Frank Lobbezoo; Corine M. Visscher; Justin Durham; Anna Lövgren (BMC, 2023)
Abstract Background Temporomandibular disorders (TMD) are common and therefore managed by dentists on a daily basis. However, patients with TMD consistently go undetected and therefore untreated in dentistry. The reasons for these shortcomings have not been fully explored, specifically with regard to patients' perspectives. Therefore, this study aimed to explore patients' experiences of TMD and related treatment, with special focus on the experiences of having TMD, factors related to seeking care, and perspectives on received treatment. Methods Purposive sampling was used to recruit adult patients at the Public Dental Health services (PDHS) in the Region of Västerbotten, Sweden, during 2019. Individual semi-structured interviews were conducted and analysed using Qualitative Content Analysis. Sixteen patients were interviewed (ten women and six men, 20-65 years). The interviews probed the patients' perspectives of having TMD, seeking care, and receiving treatment. All participants were also examined according to the Diagnostic Criteria for TMD (DC/TMD) and qualified for at least one DC/TMD diagnosis. Results The data analysis led to the main theme Seeking care when the situation becomes untenable, but dental care fails to meet all needs. The patients expressed worry and social discomfort because of the symptoms but still strived to have an as normal daily life as possible. However, severe symptoms and associated consequences compelled them to seek professional help. Experiences of distrust together with challenges to access the PDHS were identified and related to the patients' unfulfilled expectations. Conclusions Patients' reported experiences indicate that receiving timely and appropriate care is more of an unfulfilled expectation than the current state of management of patients with TMD in dentistry.